The emergence of innovative moments in narrative therapy for depression: Exploring therapist and client contributions. - Cunha, C. (2012)
Abstract. According to the narrative framework, clients seek therapeutic help due to the constricting nature of problematic self-narratives and psychotherapy should contribute to the elaboration of narrative novelties and innovative self-narratives. We term these narra- tive novelties as innovative moments (IMs) and developed the Innovative Moments Cod- ing System (IMCS) to study them in psychotherapeutic discourse, differentiating five types of IMs: action, reflection, protest, reconceptualization and performing change IMs. Previ- ous research studies using the IMCS with narrative therapy, emotion-focused therapy and client-centered therapy show that action, reflection and protest IMs appear in good (GO) and also in poor outcome (PO) cases while, reconceptualization and performing change IMs are more typical of good outcome (GO) cases. In this study, we will address how these IMs are co-constructed in the therapeutic dialogue through the discussion of three particu- lar forms of IMs’ emergence in psychotherapy. These forms of emergence refer to different degrees of client and therapist participation: (1) IMs produced by the therapist and ac- cepted by the client; (2) IMs prompted by the therapist and developed by the client; and (3) IMs spontaneously produced by the client. The exploratory analysis of three initial, three middle and three final sessions of contrasting cases (a GO and a PO) of narrative therapy for depression showed that IMs produced by the therapist were more associated to the PO case, while IMs prompted by the therapist were more associated to the GO case.